Desain User Interface dan Experience Untuk Aplikasi E-Tiket Bus Di PT.Satunusa Lintas Persada Dengan Metode Design Thinking - Lubis, M.Zein Ali; Randi Rian Putra; Heni wulandari (CV. Hawari, 2025)
Satunusa Lintas Persada is an Inter-City Inter-Provincial (AKAP) bus company located in Medan City. Currently, the ticket sales system at Satunusa Bus still uses conventional methods. With the rapid progress of information technology and innovation in the smartphone sector, various human activities are becoming easier, including ordering tickets via e-ticketing applications which allow passengers to choose tickets according to their needs. Application development begins with interface design, which is the first step to realizing the concept as well as designing the flow and work mechanism of the application. The method used in this process is design thinking, consisting of five stages: empathize, define, ideate, prototype, and test. Based on system design testing using the System Usability Scale (SUS), an average score of 91.5 was obtained which is included in the